Legal Counseling on Problems in Hazardous and Toxic Waste Management and Strategies to Overcome Environmental Pollution - Rahayu, Alya Maya Khonsa; Triwanto, Triwanto; Arantxha, Syifa Azzahra Nada; Astuti, Risma Yulia (Faculty of Law, Universitas Pattimura, 2025)
Introduction: Hazardous and Toxic Materials (B3) waste management is a crucial issue in efforts to protect the environment and public health. The main problems include low compliance with regulations, waste management that does not meet standards, lack of public awareness, weak supervision, and lack of adequate processing technology.Purposes of The Devotion: This legal counseling aims to increase the understanding and commitment of all parties in managing B3 waste responsibly, so as to prevent environmental pollution and protect public health. Method of The Devotion: Legal counseling activities are carried out by the panel discussion method where the presenter delivers the material in turn then continues with a question and answer between the speaker and the community.Results Main Findings of the Devotion: The results of the study indicate that the socialization carried out by the local government is still limited, both in terms of frequency and reach of participants. The community in Gadingan Village still has a low understanding of the importance of environmental protection based on the law. Therefore, it is necessary to increase the intensity of socialization and more active community involvement in environmental programs. This study is expected to contribute to efforts to increase community understanding of the importance of environmental management and protection in accordance with the provisions in force in Law Number 32 of 2009.